Analyzing the Interactions among Barriers to the Use of Solar Energy for Heating in Residential Buildings in Van, Turkiye - Keser, Unsal; Kerestecioglu, Server Funda (MDPI, 2024)
In terms of environmental sustainability, the barriers-and interactions between these barriers-to the use of solar energy for active and passive heating in residential buildings stem from location-specific housing production patterns and the actors involved in these patterns. A clear definition of hierarchies and priorities between barriers helps managers set strategic priorities and action plans to find solutions. After the earthquake in Van in 2011, 6000 hectares of land were opened for new development, and research using the sampling method discovered that the most common type of housing production in the city is the build-to-sell housing production method. The actors involved in build-to-sell housing production are technical staff, local-central administrations, entrepreneurs, end users, landowners, financial companies, non-governmental organizations, and building inspection institutions. This article examines the barriers to the use of solar energy for active and passive heating purposes, the interactions between these barriers using ISM and MICMAC methods, and the build-to-sell housing production method and actors. Barriers were identified through a literature review and semi-structured interviews. The barriers were further categorized under eight main headings according to their subject matter. The hierarchies of barriers in creating problems and solutions were determined using ISM and MICMAC methods and the findings were interpreted. In the City of Van, with regard to the houses produced via the build-to-sell production method, the barriers against the use of solar energy for heating purposes in houses considering active and passive methods are ranked in order of priority in creating the problem and the solution. Barriers caused by political and administrative issues are ranked first; barriers caused by social awareness and end users are ranked second; barriers caused by social and sociological events are ranked third; barriers caused by laws and regulations are ranked fourth; barriers caused by the knowledge, skills, and awareness of designers are ranked fifth; barriers caused by deficiencies in technical issues are ranked sixth; and barriers caused by economic and financial issues are ranked seventh. Even though the barrier caused by the working mode of build-to-sell productions is the largest in creating the problem, it is the least effective barrier to solving the problem in the ISM hierarchical and MICMAC schemes. The research process is presented in the Methods section.
Keywords: solar energy; active and passive solar heating; barriers; interpretive structural modeling (ISM); Cross-Impact Matrix Multiplication Applied to Classification (MICMAC); mode of housing production; IMPLEMENTATION; Energy & Fuels